2014
DOI: 10.1007/s00253-014-6086-8
|View full text |Cite|
|
Sign up to set email alerts
|

Genome sequence of Vibrio diabolicus and identification of the exopolysaccharide HE800 biosynthesis locus

Abstract: Vibrio diabolicus, a marine bacterium originating from deep-sea hydrothermal vents, produces the HE800 exopolysaccharide with high value for biotechnological purposes, especially for human health. Its genome was sequenced and analyzed; phylogenetic analysis using the core genome revealed V. diabolicus is close to another deep-sea Vibrio sp. (Ex25) within the Harveyi clade and Alginolyticus group. A genetic locus homologous to the syp cluster from Vibrio fischeri was demonstrated to be involved in the HE800 pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…As the proposed 18-gene cluster contains five glycosyltransferases, of which EPS273-H and EPS273-I belonged to mannosyl transferase and are located adjacently in the gene cluster, genes encoding EPS273-H and EPS273-I were deleted together. Deletion of eps273-H and eps273-I together just changed the polysaccharide molecular weight and homogeneity ( Figure 3 A), indicating that deletion of the two adjacent glycosyltransferases might be complemented by other glycosyltransferases present in the gene cluster, which was consistent with the previous report about expolysaccharide HE800 [ 24 ]. To some extent, the presence of five glycosyltransferases within the 18-gene cluster of P. stutzeri 273 may confer its ability to generate diversity in the glycosidic structure, which may increase its adaption to the changes of natural environment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As the proposed 18-gene cluster contains five glycosyltransferases, of which EPS273-H and EPS273-I belonged to mannosyl transferase and are located adjacently in the gene cluster, genes encoding EPS273-H and EPS273-I were deleted together. Deletion of eps273-H and eps273-I together just changed the polysaccharide molecular weight and homogeneity ( Figure 3 A), indicating that deletion of the two adjacent glycosyltransferases might be complemented by other glycosyltransferases present in the gene cluster, which was consistent with the previous report about expolysaccharide HE800 [ 24 ]. To some extent, the presence of five glycosyltransferases within the 18-gene cluster of P. stutzeri 273 may confer its ability to generate diversity in the glycosidic structure, which may increase its adaption to the changes of natural environment.…”
Section: Discussionsupporting
confidence: 91%
“…A polysaccharide gene cluster ( Figure 2 A) consisting of five GTs and 13 other genes were identified, which is similar to the symbiosis exopolysaccharide biosynthetic genes ( syp ) of Vibrio sp. reported previously [ 24 ]. Within the gene cluster, 14 genes appeared to encode proteins involved in biosynthesis, modification or export of polysaccharides ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 53%
“…Little variation in gene regulation or expression, as well as in encoded proteins could result in slight molecular structural variability of the EPS. It has already been shown that the syp gene cluster encoding the biosynthesis of EPS in V. fischeri and V. diabolicus could be widespread among Vibrionaceae [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its genome (5.04 mbp) was comprised of two chromosomes, the first (3.23 mbp) being larger than the second (1.81 mbp). Its GC content was typical of other V. diabolicus genomes (44.91%) (Goudenege et al 2014 ), except for a 182 kbp island, located on chromosome 2, which had a GC content of 40.8%. Eighty-two percentage of the island consisted of hypothetical genes.…”
Section: Resultsmentioning
confidence: 82%